2016
DOI: 10.1161/circimaging.115.003643
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Improved Glycemic Control on Cardiac Function in Type 2 Diabetes Mellitus

Abstract: Background— Patients with type 2 diabetes mellitus are at risk of heart failure. Specific therapeutic interventions for diabetic heart disease are still elusive. We aimed to examine the impact of improved glycemic control on left ventricular (LV) function in these patients. Methods and Results— A total of 105 subjects with type 2 diabetes mellitus (aged 54±10 years) and poor glycemic control received optimization of treatment for blood gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 36 publications
7
59
3
2
Order By: Relevance
“…LV diastolic dysfunction is an early manifestation of diabetic heart disease [1, 20, 21], and a subclinical impairment of diastolic function is associated with higher glucose levels [3, 19, 21]. Chronic increase in plasma glucose levels has been shown to negatively influence LV diastolic performance through different mechanisms, including alteration in mitochondrial energy metabolism and increment in myocardial oxidative stress [10, 11], LV mass increase and changes in myocardial composition [7, 8], acceleration of large artery stiffening and consequent increase in vascular load [1214].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LV diastolic dysfunction is an early manifestation of diabetic heart disease [1, 20, 21], and a subclinical impairment of diastolic function is associated with higher glucose levels [3, 19, 21]. Chronic increase in plasma glucose levels has been shown to negatively influence LV diastolic performance through different mechanisms, including alteration in mitochondrial energy metabolism and increment in myocardial oxidative stress [10, 11], LV mass increase and changes in myocardial composition [7, 8], acceleration of large artery stiffening and consequent increase in vascular load [1214].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, e′ velocity has been shown to be inversely related to serum concentration of procollagen type I carboxy-terminal propeptide [17], which is considered a marker of myocardial collagen content [18]. Previous studies have reported reduced e′ velocity of mitral annulus in asymptomatic T2DM patients [19, 20] as well as an association between e′ velocity and poor glycemic control [19, 21]. They have also demonstrated an inverse relationship between e′ velocity and LV mass or arterial stiffness [22, 23] and a direct association between diastolic e′ and systolic s′ longitudinal velocities [23].…”
Section: Introductionmentioning
confidence: 99%
“…Also in dogs with pacing induced heart failure, metformin treatment improved diastolic function as indicated by a reduced left ventricular end-diastolic pressure [29]. In patients with diabetes, improvements of glycemic control, including the use of metformin, was associated with improvements of diastolic function as measured by septal e’ [45]. Also in the setting of stable coronary artery disease, metformin use in diabetic patients was associated with improved left ventricular diastolic function as measured by mean e’ and IVRT [28].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested poor glycaemic control was associated with LV diastolic dysfunction, manifest as either lower e’ velocities or raised LV filling pressure; and/or more impaired LV systolic function with lower systolic strain [2, 8, 9]. Furthermore, we have recently demonstrated that improving glycaemic control in such patients resulted in improvement in LV systolic and diastolic function [30]. The largest improvements in the aforementioned study were seen in patients with the largest reduction in HbA1c levels, and in those with the lowest HbA1c levels at the end of the study.…”
Section: Discussionmentioning
confidence: 99%